Optimizing panel-based tumor mutational burden (TMB) measurement - Budczies, Jan; Allgäuer, Michael; Rempel, Eugen; Christopoulos, Petros; Kazdal, Daniel; Endris, Volker; Thomas, Michael; Fröhling, Stefan; Schirmacher, Peter; Stenzinger, Albrecht (Annals of oncology, 2019)
AbstractBackground. Panel sequencing based estimates of tumor mutational burden (psTMB) are increasingly replacing whole exome sequencing (WES) tumor mutationa
Gesehen am 17.12.2019